The Effect of A2E on the Uptake and Release of Calcium in the Lysosomes and Mitochondria of Human RPE Cells Exposed to Blue Light - Mao-Mei Luo; Lin Chen; Shu Wang; Chun Zeng; De-Zhi Li; YeGe Bi; Long-Qian Liu; Shan-Jun Cai (Journal of Ophthalmology)
We aimed to explore the effect of N-retinylidene-N-retinylethanolamine (A2E) on the uptake and release of calcium in lysosomes and mitochondria by establishing a model of human retinal pigment epithelial (RPE) cell injury induced by exposure to blue light. Primary human RPE cells were cultured from passages 4 to 6 and exposed to blue light at an intensity of 2000 ± 500 lux for 6 hours. After blue light exposure, the culture was maintained for 24 hours. A2E at a final concentration of 25 μM was added to the culture 2 hours before light exposure, and nifedipine at a final concentration of 10−4 M was added 1 hour before light exposure. The levels of Ca2+ in the cytosol (CaTM/2AM), mitochondria (Rhod/2AM), and lysosomes (LysoTracker Red and Fluo-3/AM) were determined. In order to measure the calcium levels in the different organelles, RPE were imaged using a laser scanning confocal microscope. Moreover, changes in the mitochondrial membrane potential were detected by flow cytometry analysis of JC-1-stained cells. The obtained results revealed that blue light illumination increased the calcium fluorescence intensity in the cytoplasm, mitochondria, and lysosomes of human RPE cells when compared with the control cells (P<0.05). After A2E treatment, the fluorescence intensity of the calcium in the cytoplasm was further increased (P<0.05), while that in the mitochondria and lysosomes decreased (P<0.05). In addition, we observed that nifedipine reduced the fluorescence intensity of calcium in the RPE cells. Our results also showed that the mitochondrial membrane potential in the RPE treated with blue light and A2E was lower than that in the control, blue light, and A2E-treated cells (P<0.05). Blue light increased calcium levels in the cytoplasm, lysosomes, and mitochondria of RPE cells. A2E damages the lysosomal and mitochondrial membranes, resulting in calcium release into the cytoplasm. Finally, our results demonstrated that both blue light and A2E treatments reduced mitochondrial membrane potential, increasing cytosolic Ca2+ levels, which can contribute to the activation of RPE death.